Astronomical Signatures of Dark Matter - Paul Gorenstein; Wallace Tucker (Advances in High Energy Physics)
Several independent astronomical observations in different wavelength bands reveal the existence of much larger quantities of matter than what we would deduce from assuming a solar mass to light ratio. They are very high velocities of individual galaxies within clusters of galaxies, higher than expected rotation rates of stars in the outer regions of galaxies, 21 cm line studies indicative of increasing mass to light ratios with radius in the halos of spiral galaxies, hot gaseous X-ray emitting halos around many elliptical galaxies, and clusters of galaxies requiring a much larger component of unseen mass for the hot gas to be bound. The level of gravitational attraction needed for the spatial distribution of galaxies to evolve from the small perturbations implied by the very slightly anisotropic cosmic microwave background radiation to its current web-like configuration requires much more mass than is observed across the entire electromagnetic spectrum. Distorted shapes of galaxies and other features created by gravitational lensing in the images of many astronomical objects require an amount of dark matter consistent with other estimates. The unambiguous detection of dark matter and more recently evidence for dark energy has positioned astronomy at the frontier of fundamental physics as it was in the 17th century.